P56 Factor Xa inhibition suppresses thioacetamide induced liver fibrosis. (16th November 2010) - Dhar, A; Anstee, Q; Sadiq, F; Levene, A; Goldin, R; Thursz, M
Abstract : Introduction: In addition to its role in activating fibrinogen, thrombin mediates cellular activation of macrophages, platelets and hepatic stellate cells via the protease-activated receptor, PAR-1. Thrombin antagonists demonstrate anti-fibrotic properties. Factor Xa (FXa), a protease which is activated earlier in the coagulation cascade, promotes connective tissue growth factor, and activates fibroblasts via PAR receptors. Direct FXa inhibition has recently been shown to significantly reduce lung fibrosis, a paradigm for hepatic fibrosis, in a bleomycin mouse model. Specific inhibition of FXa may offer additional efficacy as an anti-fibrotic in models of chronic liver injury. Aim: To evaluate the impact of FXa inhibition and thrombin antagonism on hepatic fibrosis using a thioacetamide (TAA) mouse model. Method: 45 C57BL/6J mice were administered TAA (300 mg/l) via drinking water for a period of 8 weeks to induce liver fibrosis. A subset of these animals were given Rivaroxaban, a direct FXa inhibitor (n=15), or Dagibatran, a direct thrombin antagonist (n=15). Both drugs were administered daily by oral gavage at doses to achieve prolongation of the prothrombin time. The remaining animals (n=15) received no anticoagulation, and acted as the control group. At 8 weeks livers were extracted and liver sections stained with picorsirus red and visually scored for fibrosis using an adapted Ishak Modified Histology Activity Index by a blinded histopathologist. Digital image analysis was performed to calculate the mean percentage area of fibrosis per section. Results: In control mice the mean fibrosis score was 4.08 and the mean percentage area of fibrosis was 3.76%. In comparison mice treated with FXa inhibition had a mean fibrosis score of 2.46 (p=0.008) and mean percentage area of fibrosis of 2.02% (p=0.012). In contrast mice treated with thrombin inhibition had a mean fibrosis score of 3.25 (p=0.68 vs controls), and mean percentage area of fibrosis of 3.70% (p=0.68 vs controls). Factor Xa inhibition was significantly more effective than thrombin in reducing percentage area of fibrosis (p=0.031). Conclusion: FXa inhibition significantly decreased the rate of hepatic fibrosis in a TAA model of liver fibrosis. It is likely that direct thrombin inhibition is less effective than FXa inhibition because thrombin inhibitors fail to block PAR-mediated stellate cell activation by FXa. FXa inhibition is a potential novel anti-fibrotic approach and warrants further investigation in human studies.